Wiley GAAP for Governments 2015 : Interpretation and Application of Generally Accepted Accounting Principles for State and Local Governments. - Ruppel, Warren (Wiley, 2015)
The essential reference for governmental GAAP application Wiley GAAP for Governments 2015 provides the latest information on GAAP, with coverage designed specifically for government entities. With a focus on the practical rather than the academic, this book provides insightful, up to date implementation information and explanations of the important developments in governmental GAAP that have occurred in the past year. Exclusive coverage includes school districts, public authorities, and individual pension plans financial statements, with a disclosure checklist that helps preparers ensure compl.